Isolation and Identification of Disease-Causing Fungi in Tilapia (Oreochromis niloticus) and Catfish (Clarias gariepinus) Seeds - Indra Lesmana; Nur Arlia Yusnita; Andri Hendrizal (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This study discusses the isolation and identification of disease-causing fungi in the seeds of Tilapia (Oreochromis niloticus) and Catfish (Clarias gariepinus) cultivated in the cultivation pond of Baru Ladang Bambu Village, Medan Tuntung District, North Sumatra. Sampling was carried out as much as 15 fish each. There are four types of fungi that attack tilapia and catfish. The attack rate with the highest species diversity was found in catfish with 4 types of fungi including Aspergillus flavus, Penicillium glabrum, Saprolegnia sp., and Aspergillus niger. Whereas in Tilapia the types of fungi that attack only consist of 2 types, namely Aspergillus flavus and Saprolegnia sp.